Communautés patrimoniales, pratiques musicales et enjeux de reconnaissance : le cas de la rumba catalane - Arnauld Chandivert; Hervé Parent (Transposition)
This article examines the place of the notion of community in the UNESCO policies on ICH, with regard to a project in which the authors are stakeholders: the inscription of Catalan rumba, a gypsy musical practice, under the 2003 Convention. The first part aims to characterise the “community model” present in these policies, and then considers their application in France and in the case of the rumba. After pointing out the ambiguity of this application and the issues involved, in terms of the representation of gypsy populations, the analysis focuses on the rumba itself—notably the fact that despite the evolving nature of this musical genre, certain stakeholders in certain contexts have asserted more fixist definitions of it. One such context is the inscription project, which thus appears as a space for the identification and mediation of the collective affiliations and musical practices—processes that ultimately must be integrated into the consideration of the rumba from a heritage perspective.